Bioenergy from the forest – a source of conflict between forestry and nature conservation? : an analysis of key actor’s positions in Sweden - Wallin, Ida (SLU/Dept. of Forest Products, 2012)
Bioenergy from the forest has been heavily debated in Sweden for several decades due to the interest of society to decrease dependence upon fossil fuels and limit the effects of climate change. The actual use of bioenergy from the forest has shifted over the years but increased during the last decades. Private actors within forest and nature conservation sectors play an important role for the development of bioenergy from the forest as well as for the debate and the implementation of political goals. Forestry in Sweden is characterised by ‘freedom under responsibility’ for private actors and the perspective of governance is valuable for studying actors and discourses. Actors have their own interests and goals and the study focuses on three key actors representing ownership, industrial and environmental interests respectively. The aim of the study is to describe how the key actor’s positions concerning bioenergy from the forest have developed between years 2000-2010. Positions and dominating discourses were identified by text analysis.